Multifunctionality of Calebin A in inflammation, chronic diseases and cancer - Brockmueller, Aranka; Mueller, Anna-Lena; Kunnumakkara, Ajaikumar B.; Aggarwal, Bharat B.; Shakibaei, Mehdi (Frontiers in Oncology, 2022)
Chronic diseases including cancer have high case numbers as well as mortality rates. The efficient treatment of chronic diseases is a major ongoing medical challenge worldwide, because of their complexity and many inflammatory pathways such as JNK, p38/MAPK, MEK/ERK, JAK/STAT3, PI3K and NF-kB among others being implicated in their pathogenesis. Together with the versatility of chronic disease classical mono-target therapies are often insufficient. Therefore, the anti-inflammatory as well as anti-cancer capacities of polyphenols are currently investigated to complement and improve the effect of classical anti-inflammatory drugs, chemotherapeutic agents or to overcome drug resistance of cancer cells. Currently, research on Calebin A, a polyphenolic component of turmeric (Curcuma longa), is becoming of growing interest with regard to novel treatment strategies and has already been shown health-promoting as well as anti-tumor properties, including anti-oxidative and anti-inflammatory effects, in diverse cancer cells. Within this review, we describe already known anti-inflammatory activities of Calebin A via modulation of NF-kB and its associated signaling pathways, linked with TNF-α, TNF-β and COX-2 and further summarize Calebin A’s tumor-inhibiting properties that are known up to date such as reduction of cancer cell viability, proliferation as well as metastasis. We also shed light on possible future prospects of Calebin A as an anti-cancer agent.